Comparing Customer Loyalty Formation in Coffee-To-Go and Slow Bar Coffee Shops: The Roles of Price, Service, and Brand Experience - Anakisida Huda Mas'ud; Tulus Haryono (MASI Mandiri Edukasi, 2026)
The rapid expansion of the coffee shop industry in Yogyakarta has been accompanied by a shift in business orientation from efficiency-driven coffee-to-go outlets to experience-oriented slow-bar coffee shops, creating distinct patterns in customer loyalty formation. This study aims to compare how brand experience, customer service perception, and customer price perception influence customer loyalty, with trust and satisfaction acting as mediating variables across the two coffee shop models. A quantitative research design was applied using survey data collected from 240 coffee shop customers in Yogyakarta. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) and supported by Multi-Group Analysis (MGA) to identify differences between coffee-to-go and slow bar segments. The findings reveal that the mechanisms underlying loyalty formation vary significantly between the two models. In coffee-to-go shops, customer price perception and service perception have a stronger impact on satisfaction and loyalty, whereas in slow bar coffee shops, brand experience and trust play a more prominent role. Trust and satisfaction are empirically validated as significant mediating variables in both contexts. These results indicate that different business models require distinct strategic approaches to effectively strengthen customer loyalty.